Sarconesiopsis magellanica (Diptera: Calliphoridae) excretions and secretions have potent antibacterial activity (2014)
The most important mechanism for combating infection using larval therapy depends on larval excretions and secretions (ES). The present work was aimed at evaluating Sarconesiopsis magellanica (Diptera: Calliphoridae) ES antibacterial activity in six bacterial strains (three Gram-positive and three Gram-negative) and comparing this to the effect of Lucilia sericata-derived ES. Antibacterial activity at 50. ?g/mL minimum inhibitory concentration (MIC) was observed for Staphylococcus epidermidis ATCC-12228 and Staphylococcus aureus ATCC-29213 strains, when the turbidimetry test involving S. magellanica ES was used; the rest of the bacterial strains (Staphylococcus aureus ATCC-6538, Pseudomonas aeruginosa ATCC-10145, Pseudomonas aeruginosa ATCC-9027 and Pseudomonas aeruginosa ATCC-27853) were inhibited at a 100. ?g/mL MIC. Twice the amount was required to inhibit the aforementioned bacteria with L. sericata-derived ES using this same technique; a similar trend was observed when the agar diffusion method was used instead. Furthermore, when the previously established MIC for each bacterial strain was used, their colonies became reduced following 1-6. h incubation with S. magellanica derived ES, whilst the reduction occurred from 2 to 6. hours with those from L. sericata. Although the MIC for each strain obtained with ciprofloxacin was lower than those established when using either blowfly derived-ES, the gradual reduction of the colonies occurred at a longer incubation time (6. h or more). The results showed that S. magellanica ES antibacterial activity was more potent and effective, compared to that of L. sericata-derived ES. © 2014 Elsevier B.V.